2009
DOI: 10.1038/leu.2009.104
|View full text |Cite
|
Sign up to set email alerts
|

AML1-ETO9a is correlated with C-KIT overexpression/mutations and indicates poor disease outcome in t(8;21) acute myeloid leukemia-M2

Abstract: AML1-ETO fusion gene is generated from chromosomal translocation t(8;21) mainly in acute myeloid leukemia M2 subtype (AML-M2). Its spliced variant transcript, AML1-ETO9a, rapidly induces leukemia in murine model. To evaluate its clinical significance, AML1-ETO9a expression was assessed in 118 patients with t(8;21) AML-M2, using qualitative and nested quantitative reverse transcriptase (RT)-PCR methods. These cases were accordingly divided into the AML1-ETO9a-H group (n ¼ 86, positive for qualitative RT-PCR, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 25 publications
5
56
1
1
Order By: Relevance
“…S8 B and C). Our result that none of the 23 randomly selected t(8;21) patient samples has detectable 9a protein predicts that between 0% and 14.3% of t(8;21) patients express 9a protein (Wilson method with 95% confidence), which is significantly lower than the reported percentage (∼70%) of patients harboring the 9a transcript (binomial exact test P value < 0.05) (14,16). Collectively, these data underscore the significance of oncogene expression to disease phenotype and suggest that, whereas AE9a is a potent oncogene at high expression levels in murine transduction/transplantation assays, its contribution to t(8;21) disease requires careful verification.…”
Section: Coexpression Of Ae and Ae9a In Human Cells Results In Ae Domcontrasting
confidence: 51%
See 2 more Smart Citations
“…S8 B and C). Our result that none of the 23 randomly selected t(8;21) patient samples has detectable 9a protein predicts that between 0% and 14.3% of t(8;21) patients express 9a protein (Wilson method with 95% confidence), which is significantly lower than the reported percentage (∼70%) of patients harboring the 9a transcript (binomial exact test P value < 0.05) (14,16). Collectively, these data underscore the significance of oncogene expression to disease phenotype and suggest that, whereas AE9a is a potent oncogene at high expression levels in murine transduction/transplantation assays, its contribution to t(8;21) disease requires careful verification.…”
Section: Coexpression Of Ae and Ae9a In Human Cells Results In Ae Domcontrasting
confidence: 51%
“…Furthermore, disease relapse is significantly correlated with higher transcript levels (39)(40)(41)(42). Similarly, high transcript levels of AE9a also correlated with t(8;21) disease relapse (16,43 signals from cooperating events play a role in how AE or AE9a affect downstream signals. A number of cooperating oncogenes have been shown to promote leukemic transformation with full-length AE (6,(8)(9)(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S9). In t(8;21) AML, AE and AE9a are associated with C-KIT mutation/overexpression (8,11), and AE is able to up-regulate C-KIT (8). Therefore, BOR represents a C-KIT, AE/AE9a double targeting agent that triggers a positive feedback signal network to induce apoptosis, and its efficacy on the murine t(8;21) AML model suggests its potential of clinical application in t(8;21) AML as well as other C-KIT-driven cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The t(8;21), which represents the most common chromosomal anomaly in AML, targets eight twenty one [ETO, also known as myeloid transforming gene on chromosome 8 (MTG8) or RUNX1T1] on chromosome 8 and acute myeloid leukemia 1 [AML1, also known as Runt-related transcription factor 1 (RUNX1), core binding factor (CBF) α2, and Phosphatidylethanolamine-binding protein (PEBP) 2αB] on chromosome 21, yielding two fusion transcripts, the AML1-ETO (AE) (9) and AML1-ETO9a (AE9a), lacking the neuralized homology repeat (NHR)3-4 domains at the C terminus of ETO moiety (10). It has been established that AE9a bears a much stronger leukemogenic activity than AE in murine system (10), and a similar situation might exist in human setting (11). Studies showed that t(8;21) AML follows a stepwise leukemogenesis (i.e., AE/AE9a represent the first, fundamental genetic hit to initiate the disease), whereas activation of the C-KIT pathway may be a second but also crucial hit for the development of a full-blown leukemia (8,12).…”
mentioning
confidence: 99%